Challenges in dental education - Thomas, Anjana (Indonesian Journal of Prosthodontic, 2024)
Dental education faces numerous challenges that significantly affect the training and preparedness of future dental professionals. This article highlights the primary obstacles and proposes potential solutions to address them. The rapid advancement of technology necessitates continuous updates to curricula, incorporating innovations such as digital imaging, CAD/CAM systems, and laser dentistry. Ensuring faculty and student proficiency in these technologies requires substantial investment in training and resources.In summary, addressing these challenges requires curriculum reform, investment in technology, enhanced clinical training opportunities, financial support mechanisms, mental health initiatives, and adaptable Dental education faces numerous challenges that significantly affect the training and preparedness of future dental professionals. This article highlights the primary obstacles and proposes potential solutions to address them.